Impact of mydriatic eye drops on neonatal cerebral blood flow - Atef Alshafei; Mahmoud Ahmed; Shymaa Farouk; Ahmed Gouda; Anwar Khan; Rashid Mustafa (Hygeia Press di Corridori Marinella, 2017)
Retinopathy of prematurity (ROP) screening is a common routine procedure carried out on preterm infants in neonatal intensive care units (NICUs). Mydriatic eye drops containing phenylephrine hydrochloride 2.5% (a sympathomimetic agent) and tropicamide 0.5% (a cycloplegic medication) are readily absorbed from the conjunctiva and produce systemic responses in various organs. To our knowledge, no studies have investigated the direct effects of these medications on cerebral blood flow velocities (CBFVs) in preterm infants. To evaluate the systemic effects of locally instilled mydriatic eye drops (phenylephrine hydrochloride 2.5% and tropicamide 0.5%) used for ROP screening, on cerebral blood flow velocity in preterm infants, a prospective observational study was conducted among preterm infants with gestational age (GA) < 31 weeks admitted to the NICU at Dubai Hospital between February 20, 2017 and June 20, 2017. The infants (at a post-menstrual age of 31-34 weeks) underwent duplex ultrasound evaluation of CBFV before and after mydriatic eye drops administration. Pulsed-wave Doppler ultrasound studies were performed 1 h before and 1 h after eye mydriasis. We measured peak systolic velocity (PSV) and end diastolic velocity (EDV) for both the anterior cerebral artery (ACA) and middle cerebral artery (MCA) and calculated the resistive index (RI), defined as PSV - EDV/PSV. Mean arterial blood pressure (MAP), heart rate, oxygen saturation and pain score were assessed before and 1 h after ROP examination. A paired t-test and McNemar's test were used to assess the statistical significance of the difference between pairs of means and the qualitative variables measured twice for the same study group. Among the 42 eligible preterm infants, the mean (SD) GA was 27 (2.68) weeks (range, 24-31 weeks). The mean (SD) RI of ACA before and 1 h after eye drops administration was 0.84 (0.06) and 0.83 (0.07) respectively (p = 0.453). The mean (SD) RIs of MCA before and then 1 h after mydriasis were 0.83 (0.05) and 0.83 (0.09), respectively (p = 0.559). Phenylephrine hydrochloride 2.5% and tropicamide 0.5% eye drops for neonatal ROP screening were not associated with significant changes in CBFVs. There was no effect on pain score or hemodynamic stability in the preterm infants.